EFEKTIFITAS JAKSA PENGACARA NEGARA DALAM UPAYA PEMULIHAN KEUANGAN NEGARA/DAERAH SEBAGAI AKIBAT TINDAK PIDANA KORUPSI DI KEJAKSAAN NEGERI PURWOKERTO - Sutrisno Sutrisno (MIH Unsoed, 2018)
Based on the result of the research and a discussion to the main problem that proposed, therefore we can make some conclusion: The effectivity of State attorney On The Refund of State/Region Monetary Due To Corruption Act In The State Attorney Office Purwokerto, which purpose is to return the loss of state fund or state economy due to corruption act, if we review it from the effectivity of State attorney as one of the state instrument to return the state/region economy as a result of corruption act by using UU No 3 Tahun 1971 about Eradication of Corruption Act In The State Attorney Office Purwokerto, we can say that it hasn’t effective yet, due to Litigation process handled by State attorney which filed civil action to the District Court, no one is capable to pay the loss of state/region due to corruption act in civil ruling, because the defendent already has no possession. Then, on Non Litigation way, using State attorney instrument, a little bit effective even though has to pay replacement money by credit because the defendant is capable to pay off the replacement. If we use UU No 31 Tahun 1999 that has been changed and replaced to UU No 20 Tahun 2001 about the Changes on UU No 31 Tahun 1999 about Erradication of Corruption Act to a State Attorney, it won’t be a problem because if the defendant is not capable of paying the replacement money based on the decision, the defendant will undergo the subsidiary criminal in the form of penalty, which is the period of time will not exceed the main criminal threat dan the period of time has already decided on the decision.That factors become obstacles, is the State Attorney will not able to perform a sequest sizing because the defendant is unable and has no possession in a nominal of money being corrupted, then from the Law enforcer itself, that the State Attorney is having difficulties to track posession that belongs to the defendant which is gain from the corruption act or assume gained from the corruption act, while the obstacles from the society, there is a lack of awareness from the society itself, which is a lack of concern to give information earlier and detail on the possession belong to the defendant to the law enforcer to a person a suspected as a corruption perpetrators.